2017
DOI: 10.21834/e-bpj.v2i6.961
|View full text |Cite
|
Sign up to set email alerts
|

Fire Safety Management System for Heritage Buildings in Malaysia

Abstract: Fire is one of the horrific events that could lead to death and total destruction of buildings. Many great buildings were lost on fire. Many towns and cities were rebuilt because of great fires. Heritage buildings are recognized as over 50 years of age and built with distinct architectural features of its time. Nonetheless, these buildings present a great risk as it is often not well prepared for current fire hazard. This paper reviews the fire safety management system for heritage buildings in Malaysia based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The government must legally enforce sanctions for those who do not apply the assembly point rules. The findings are in accordant with Roslan & Said (2017).…”
Section: Figure 3 Risk Responsessupporting
confidence: 86%
See 1 more Smart Citation
“…The government must legally enforce sanctions for those who do not apply the assembly point rules. The findings are in accordant with Roslan & Said (2017).…”
Section: Figure 3 Risk Responsessupporting
confidence: 86%
“…When inspecting the safety and access of the buildings, the buildings are tested with their potential threats to the user's health and safety. The tests include the strength of carrying capacity of the structural load to resist in case of fire (Roslan & Said, 2017), the availability of fire extinguishers, access to self-rescue, climate risk, and financial risk. Fire disaster is still the problem in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…While most of the responses for Fire Safety Practices seem to be high among the workers, there is still the chance to improve the quality of electrical units and cables to effectively check fire in hotel environments. (Hassanain, Al-Harogi, et al, 2022;Ivanov, Chow, Yue, Tsang, & Peng, 2022;Roslan & Said, 2017). According to the finding, most hotels have fire sprinklers, emergency exits, assembly (Muster) points, emergency procedures, and telephone numbers; suitable fire extinguishers are in place, and associated pumps are in good shape and up-to-date.…”
Section: Fire Safety Management Practicesmentioning
confidence: 99%
“…Studied had revealed that many fire incidence occurs in an office building (Rahadi, 2015). The effect of the incidents on Nigeria's economic from both financial and public image viewpoints could be considerable (Roslan, 2017). These incidents happen particularly among the occupants and visitors to buildings, while they visit or carrying out their daily activities.…”
Section: Fire Safety Protection and Prevention Measuresmentioning
confidence: 99%